2020
DOI: 10.1177/0300060520946515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic value of platelet indices in pediatric acute appendicitis

Abstract: Objective Abdominal examination findings in pediatric acute appendicitis (AA) significantly vary by age. Therefore, grading systems have been developed for diagnosing pediatric appendicitis, and laboratory and radiological findings have an important role in this diagnosis. However, there is a need to develop new parameters for diagnosing AA. This study aimed to investigate the diagnostic value of platelet indices in AA. Methods This retrospective, observational study included 207 pediatric patients who were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…The study discovered that kids with AA had significantly lower MPV values (p <0.001) [26] . The current findings are in line with those of Oktay et al [27] who split 207 pediatric patients into three groups (non-AA, uncomplicated AA, and complicated AA). The non-AA group had the greatest mean MPV, and there was a statistical significance in MPV across the groups (p = 0.047).…”
Section: Discussionsupporting
confidence: 92%
“…The study discovered that kids with AA had significantly lower MPV values (p <0.001) [26] . The current findings are in line with those of Oktay et al [27] who split 207 pediatric patients into three groups (non-AA, uncomplicated AA, and complicated AA). The non-AA group had the greatest mean MPV, and there was a statistical significance in MPV across the groups (p = 0.047).…”
Section: Discussionsupporting
confidence: 92%
“…Uyanik et al confirm that MPV in children with acute appendicitis has no diagnostic value [18]. However, Oktay et al found that low MPV showed importance for the diagnosis of acute appendicitis [31]. Bilici et al also reported a significant reduction in MPV in the group of children with acute appendicitis in comparison with the control group [32].…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective study was conducted in Turkey. It included 207 pediatric patients who were divided into three groups (non-AA, uncomplicated AA, and complicated AA) [ 20 ]. The mean MPV was highest in the non-AA group, and there was a significant difference in the MPV among the groups ( p = 0.047).…”
Section: Resultsmentioning
confidence: 99%
“…This validated 27-point scale has four domains of assessment with minimum and maximum scores of 0 and 32, respectively. Based on these scores, the risk of bias was graded as low (score > 23), moderate (16)(17)(18)(19)(20)(21)(22)(23), or high (0-15). The kappa statistics were used to identify the level of inter-rater agreement regarding the risk of bias [11].…”
Section: Quality Assessmentmentioning
confidence: 99%